Implications of the Sustainable Development Goals on national energy demand: The case of Indonesia. (1st April 2020) - Santika, Wayan G.; Anisuzzaman, M.; Simsek, Yeliz; Bahri, Parisa A.; Shafiullah, G.M.; Urmee, Tania
Abstract: Energy is a key enabling factor within the Sustainable Development Goals (SDGs), which include eradicating poverty and hunger, improving human well-being, and protecting the environment. Countries intending to incorporate SDGs in their development programs should expect an increase in energy consumption, and therefore, need to review their energy planning. The objective of this paper is to anticipate the additional energy requirements of Indonesia with the implementation of SDGs compared to business as usual (BAU) and current policy (CP) scenarios. Assuming all SDG targets were to be implemented in the Indonesian national development plan, the additional energy demand for each target by 2030 was calculated. It was found that 18 out of 169 SDGs targets required additional energy in the Indonesian context. Overall, more energy will be needed to achieve those 18 SDGs targets compared to the BAU scenario. Fortunately, the full realisation of the current energy policies will cover the additional energy required under the SDGs scenario. Highlights: Energy demand in Indonesia under the SDGs will increase by 5% of the BAU in 2030. Under the national energy plan, the energy demand will be 19% higher than the BAU. The national energy plan has anticipated energy demand under the SDGs scenario. The current energy policy scenario calls for a dramatic increase in electricity use.